A comparative study of single and double dose of intracervical Prostaglandin E2 gel for cervical ripening - Smita Parate; Juzar Fidvi (International Journal of Medical Research and Review, 2015)
Introduction: Induction of labour should be safe for both the mother and baby that is a method with short induction delivery interval, absence of side effects and conveniences for both the patients and medical staffs. A lamp of success was lit with the introduction of prostaglandins, one of the factor that influences successful induction of labor.Material & methods: A case control study was carried out in department of obstetrics and gynecology in tertiary care teaching hospital of North India. A total 100 patients were taken in two groups, 50 patients of study group were induced with two doses of PGE2 gel, 6 hours apart and 50 patients of control group were induced with single dose of PGE2 gel given intracervically.Results: In this study age group of the patients ranges from 18-35 years and the parity was up to para 4. It was evident that major indication of induction of labor was PIH and post dated pregnancies. All the patients had Bishop score 4 or less indicating an unripe cervix. There was significant increase in mean Bishop score after second dose instillation in study.ie 6.84 as compared to control group where second dose were not instilled. Mean induction delivery interval in study group is 13.14 hrs as compared to controls 16.37 hrs. 25 out of 50 patients in study group delivered within 12 hrs as compared to 6 out of 50 patients in control groups.Conclusion: The above study concluded that intracervical double dose of PGE2 gel is significantly effective for pre induction cervical ripening and 94% of patients went into labor spontaneously without requiring stimulation by other oxytosis.